0522 Level II Home Sleep Apnea Testing Compared to In-Lab Polysomnography for the Evaluation of Obstructive Sleep Apnea in Youth with Down Syndrome. (25th May 2022) - Cielo, Christopher; Kelly, Andrea; Ward, Michelle; Falvo, Jennifer; Arputhan, Ahtish; Walega, Rachel; Xanthopoulos, Melissa; Tapia, Ignacio
Abstract: Introduction: In-laboratory polysomnography (PSG) is recommended for obstructive sleep apnea (OSA) diagnosis in children. However, cost, insufficient facilities, and disruption to families challenge PSG completion, particularly for youth with disabilities such as Down syndrome (DS) in whom OSA is common. By providing sleep architecture and arousal-associated hypopnea data, level II home sleep apnea testing (HSAT) with EEG has the potential to be accessible and accurate. We hypothesized that compared to PSG, HSAT would be accurate in detecting moderate-severe OSA in youth with DS and preferred by families. Methods: Prospective comparative effectiveness study. Youth <18 years old with DS underwent in-laboratory PSG and level II HSAT at home. Parents completed questionnaires assessing feasibility, acceptability, and test preference. HSAT, scored using AASM criteria blinded to PSG result, were compared to reference PSG. OSA was defined as obstructive apnea hypopnea index (OAHI) greater than 5 events per hour on either test. Results: Thirty-five (17 female) youth aged [median (IQR)] 10.0 (6.1, 16.9) years completed testing. Total sleep time for HSAT was 7.9 (6.9, 8.9) hours versus 6.8 (5.9, 7.0) hours for PSG (p=0.002). PSG OAHI was 12.7/hr (5.3, 21.5). Twenty-six (74.3%) participants had OSA by PSG, 20 of whom were correctly identified by HSAT; one participant with OSA diagnosed by HSAT (OAHI=6.2/hr) was not identified by PSG (OAHI=3.9/hr). Accuracy of HSAT for identifying OSA was 80.0%, sensitivity 76.9%, and specificity 88.9% compared to PSG. Signal quality was good except for pulse oximetry, with median (IQR) adequate signal for 79.5% (57.5%, 86.3%) of the study. Compared to PSG, 83.3% of parents reported that youth had a more normal night's sleep with HSAT, 70.0% of parents found HSAT easier, and 90.0% of youth preferred HSAT. Conclusion: In youth with DS, HSAT has good accuracy for detecting moderate-severe OSA. Limitations may include night-to-night variability, differences in environment, or loss of oximetry signal. Youth slept more during HSAT than in-lab PSG and the majority of families preferred level II HSAT. Level II HSAT could provide a means for expanding the evaluation of OSA in youth with DS. Support (If Any): NIH R21HD101003 (Tapia/Kelly)